P161 SUSTAINABLE IMPROVEMENTS IN URGENT CARE ACCESS AND OUTCOMES FOR PATIENTS WITH INFLAMMATORY BOWEL DISEASE THROUGH IMPLEMENTATION OF AN URGENT ACCESS TOOLKIT. (18th January 2018) - Hou, Jason K; Gonzalez, Iliana; Xu, Ang; Weatherly, Julie; Shukla, Richa; Sellin, Joseph; Cruz, Guillermina; Crate, Damara; Adams, Kelly McCutcheon; Weaver, Alandra; Melmed, Gil Y; Siegel, Corey A
Abstract: Background: Patients with inflammatory bowel disease (IBD) without adequate access to urgent medical care for exacerbation of symptoms tend to obtain care from emergency departments (ED), which is associated with an increased use of opiates, steroids, and poor patient satisfaction. We previously described the development of an urgent access toolkit using a Breakthrough Series (BTS) Collaborative as part of IBD Qorus. The aim of this study was to demonstrate the sustainability and clinical impact of implementation of the urgent access toolkit after 1 year. Methods: The urgent access toolkit consisted of an urgent care hotline for direct patient access to a nurse, and patient educational processes. Data were collected from July 2015 through February 2017 from patients at the Baylor College of Medicine IBD clinic. The urgent access toolkit was implemented in December 2015. The baseline period was considered prior to December 2015 and the post-implementation period was after December 2015. Outcomes were assessed using run charts. Results: A total of 1663 patient encounters were included in the study period, including 438 encounters in the baseline time period and 1225 encounters in the post-implementation period. In the baseline period, a median of 22% of patients reported ED visits, 24% with CT scans, 18% with IBD-related hospitalizations, 17% of patients on prednisone, and 11% on narcotics. Run charts after implementation of the toolkit demonstrated shifts in reduction in ED visits (Fig1), CT scans(Fig2), prednisone use, and an increase in patient satisfaction related to IBD urgent care. Conclusions: Implementation of the urgent access toolkit reduces IBD-associated ED visits, CT scans, and prednisone use, as well as increases patient satisfaction related to urgent care access. These improvements can be sustained for 1 year. Participation in a learning health system facilitates sustainable improvements in access to urgent IBD care and related outcomes.